2019
DOI: 10.3390/ijms21010229
|View full text |Cite
|
Sign up to set email alerts
|

Food-Derived Collagen Peptides, Prolyl-Hydroxyproline (Pro-Hyp), and Hydroxyprolyl-Glycine (Hyp-Gly) Enhance Growth of Primary Cultured Mouse Skin Fibroblast Using Fetal Bovine Serum Free from Hydroxyprolyl Peptide

Abstract: Prolyl-hydroxyproline (Pro-Hyp) and hydroxyprolyl-glycine (Hyp-Gly) appear in human blood after ingestion of collagen hydrolysate and trigger growth of fibroblasts attached on collagen gel, which has been associated with beneficial effects upon ingestion of collagen hydrolysate, such as improvement of skin and joint conditions. In the present study, inconsistent results were obtained by using different lots of fetal bovine serum (FBS). Fibroblasts proliferated in collagen gel without adding Pro-Hyp and Hyp-Gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…The latter two compounds are readily separated by the m/z values of the precursor ions. The non‐spiked serum sample clearly shows the high endogenous levels of two of the analytes (B: p and G: P p ), which agrees with the findings by Asai et al 28 Compound H, the tripeptide EVF injection standard, can be used to assess the internal standard signals when unforeseen issues occur during a future analytical run. The internal standards are all present at the same concentration in the internal standard mix and in the end extract (145 ng/mL, expressed as analyte).…”
Section: Resultssupporting
confidence: 89%
“…The latter two compounds are readily separated by the m/z values of the precursor ions. The non‐spiked serum sample clearly shows the high endogenous levels of two of the analytes (B: p and G: P p ), which agrees with the findings by Asai et al 28 Compound H, the tripeptide EVF injection standard, can be used to assess the internal standard signals when unforeseen issues occur during a future analytical run. The internal standards are all present at the same concentration in the internal standard mix and in the end extract (145 ng/mL, expressed as analyte).…”
Section: Resultssupporting
confidence: 89%
“…However, daily intakes of food-derived collagen peptides enhance the growth of fibroblasts. Pro-Hyp and Hyp-Gly dipeptides play an important role in the proliferation of fibroblasts [119]. It has been demonstrated that the rest of the fragmented collagen inhibits synthesis of procollagen by fibroblasts, blocks their proliferation, induces a senescent fibroblastic morphology, and stimulates the expression of matrix metalloproteinases (MMP) [120].…”
Section: Enhancement Of Fibroblast Production and Extracellular Matrimentioning
confidence: 99%
“…In cell culture systems, fibroblasts proliferate on plastic substrate in the presence of fetal bovine serum (FBS), which is rich in protein growth factors and fibronectin. The removal of low molecular weight compounds from FBS does not affect the growth of fibroblasts on the plastic substrate (Asai et al, 2020a ). Fibroblasts have to attach to the substrates for survival.…”
Section: Introductionmentioning
confidence: 99%
“…In cell culture systems using non-coated culture plates, fibroblasts are attached to the plate surface via fibronectin, which is present in FBS and promote cell proliferation (Hayman and Ruoslahti, 1979 ). However, some researchers have used collagen gel-coated plates for the cultivation of fibroblasts (Yoshisato et al, 1985 ; Nishiyama et al, 1989 ; Kono et al, 1990 ; Shigemura et al, 2009 ; Asai et al, 2020a , b ). The collagen solution becomes to be polymerized at neutral pH after incubation at 37°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation